Incremental net monetary benefit of ocrelizumab relative to subcutaneous interferon β-1a. (3rd October 2017) - Frasco, Melissa A.; Shih, Tiffany; Incerti, Devin; Diaz Espinosa, Oliver; Vania, Diana K.; Thomas, Nina
Abstract: Aim: Disease-modifying therapies (DMTs) impact the natural history of relapsing forms of multiple sclerosis (RRMS) by reducing annual relapse rates and slowing disability progression. The effect of DMTs on indirect costs has not been consistently explored in cost-effectiveness studies thus far. The value to patients of an emerging DMT, ocrelizumab, was quantified in comparison to subcutaneous interferon beta-1a (IFN β SC) for the prevalent RRMS population with mild-to-moderate disability in the US, based on two Phase 3 trials, OPERA I and OPERA II, of ocrelizumab vs IFN β SC in RRMS. Materials and methods: A Markov model was developed to compare disability progression as measured by Expanded Disability Status Scale (EDSS) and relapse outcomes over a 30-year horizon for ocrelizumab vs IFN β SC. Direct, indirect, and informal costs (2016 US dollars) and utilities for EDSS health states were obtained from the literature. Hazard ratios for disability progression and relapse rates were estimated from clinical trials. Value was assessed by calculating the net monetary benefit (NMB), defined as the monetary value of discounted quality-adjusted life years (QALYs) minus total costs, where the value of a QALY was 150, 000. One-way sensitivity analyses were conducted. Results: Ocrelizumab was associated with an incremental gain of 0.84 QALYs and cost savings of 287, 713 relative to IFN β SC, resulting in an incremental NMB (INMB) of 413, 611 per person over 30 years. The INMB increased by 151, 763 for those initiating ocrelizumab at EDSS level 1 vs level 4. Influential parameters were QALY value, treatment costs, and disability progression; however, all sensitivity analyses indicated that the INMB for ocrelizumab relative to IFN β SC was ≥300, 000 per person. Conclusions: Ocrelizumab provides greater value to RRMS patients compared with IFN β SC. Initiating ocrelizumab at lower EDSS levels leads to a greater cumulative value due to slower disability progression, which extends years with higher quality-of-life.